Case report: Adult patient with WWOX developmental and epileptic encephalopathy: 40 years of observation - Teplyshova, Anna; Sharkov, Artem (Frontiers in Genetics, 2024)
WWOX developmental and epileptic encephalopathy is characterised by drug-resistant epilepsy with onset within the first year of life and severe psychomotor developmental delay. This report presents for the first time a clinical case of an adult patient with a homozygous likely pathogenic variant (p.Thr12Met) in the WWOX gene, with more than 40 years of follow-up. The patient had refractory epilepsy with various types of seizures during his life: mainly epileptic spasms, autonomic, myoclonic, tonic seizures, and absences. The patient had a prominent developmental delay with a lack of expressive speech, but by the age of 3, he had acquired the skills to sit, crawl, and walk with support. In adolescence, there was an acute regression of acquired skills to a total absence of independent motor activity. The patient had dysmorphic features, such as upslanting palpebral fissures, arched eyebrows, and hypertelorism. For many years, the patient was given a diagnosis of cerebral palsy; 38 years after the onset of the disease, he was given a molecular genetic diagnosis of WWOX-associated developmental and epileptic encephalopathy. Our observation illustrates the natural history of WWOX-DEE and the high clinical significance of early genetic diagnostics for identifying the cause of developmental delay and resistant epilepsy.